Mobile Elements Shape Plastome Evolution in Ferns - Robison, Tanner A (Genome Biol Evol, 2018)
Plastid genomes display remarkable organizational stability over evolutionary time. From green algae to angiosperms, most plastid genomes are largely collinear, with only a few cases of inversion, gene loss, or, in extremely rare cases, gene addition. These plastome insertions are mostly clade-specific and are typically of nuclear or mitochondrial origin. Here, we expand on these findings and present the first family-level survey of plastome evolution in ferns, revealing a novel suite of dynamic mobile elements. Comparative plastome analyses of the Pteridaceae expose several mobile open reading frames that vary in sequence length, insertion site, and configuration among sampled taxa. Even between close relatives, the presence and location of these elements is widely variable when viewed in a phylogenetic context. We characterize these elements and refer to them collectively as Mobile Open Reading Frames in Fern Organelles (MORFFO). We further note that the presence of MORFFO is not restricted to Pteridaceae, but is found across ferns and other plant clades. MORFFO elements are regularly associated with inversions, intergenic expansions, and changes to the inverted repeats. They likewise appear to be present in mitochondrial and nuclear genomes of ferns, indicating that they can move between genomic compartments with relative ease. The origins and functions of these mobile elements are unknown, but MORFFO appears to be a major driver of structural genome evolution in the plastomes of ferns, and possibly other groups of plants.